Oxidative Stress Induces Mitochondrial Compromise in CD4 T Cells From Chronically HCV-Infected Individuals - Schank, Madison; Zhao, Juan; Wang, Ling; Nguyen, Lam Ngoc Thao; Cao, Dechao; Dang, Xindi; Khanal, Sushant; Zhang, Jinyu; Zhang, Yi; Wu, Xiao Y.; Ning, Shunbin; Gazzar, Mohamed El; et al. (Frontiers in Immunology, 2021)
We have previously shown that chronic Hepatitis C virus (HCV) infection can induce DNA damage and immune dysfunctions with excessive oxidative stress in T cells. Furthermore, evidence suggests that HCV contributes to increased susceptibility to metabolic disorders. However, the underlying mechanisms by which HCV infection impairs cellular metabolism in CD4 T cells remain unclear. In this study, we evaluated mitochondrial mass and intracellular and mitochondrial reactive oxygen species (ROS) production by flow cytometry, mitochondrial DNA (mtDNA) content by real-time qPCR, cellular respiration by seahorse analyzer, and dysregulated mitochondrial-localized proteins by Liquid Chromatography-Mass Spectrometry (LC-MS) in CD4 T cells from chronic HCV-infected individuals and health subjects. Mitochondrial mass was decreased while intracellular and mitochondrial ROS were increased, expressions of master mitochondrial regulators peroxisome proliferator-activated receptor 1 alpha (PGC-1α) and mitochondrial transcription factor A (mtTFA) were down-regulated, and oxidative stress was increased while mitochondrial DNA copy numbers were reduced. Importantly, CRISPR/Cas9-mediated knockdown of mtTFA impaired cellular respiration and reduced mtDNA copy number. Furthermore, proteins responsible for mediating oxidative stress, apoptosis, and mtDNA maintenance were significantly altered in HCV-CD4 T cells. These results indicate that mitochondrial functions are compromised in HCV-CD4 T cells, likely via the deregulation of several mitochondrial regulatory proteins.